Cohort size and transitions into the labour market - Duncan Roth (Philipps-University Marburg, School of Business and Economics, 2017)
This paper estimates the effect that the size of an individual's labour-market entry cohort has on the subsequent duration of search for employment. Survival-analysis methods are applied to empirically assess this relationship using a sample of apprenticeship graduates who entered the German labour market between 1999 and 2012. The results suggest that apprentices from larger graduation cohorts take less time to find employment, but this effect appears to be significant only for a period of up to six months after graduation. These results therefore do not support the cohort-crowding hypothesis that members of larger cohorts face depressed labour-market outcomes. Moreover, there is no evidence that shorter search durations are the result of graduates being pushed into lower-quality employment. The finding that graduating as part of a larger cohort leads to shorter search durations is in line with those parts of the cohort-size literature that find larger youth cohorts being associated with lower unemployment rates. A possible explanation is that firms react to an anticipated increase in the number of graduates by creating jobs.
Keywords: J21; J64; R23; 330; survival analysis; entry conditions; cohort size; apprentices; search duration